Modified Mathematical Model of Tumor Treatment by Radiotherapy - Saad Naji AL- Azzawi; Fatima Ahmed Shihab (مجلة بغداد للعلوم, 2020)
In this research, a mathematical model of tumor treatment by radiotherapy is studied and a new modification for the model is proposed as well as introducing the check for the suggested modification. Also the stability of the modified model is analyzed in the last section.